Navodila za predmet Družinska medicina I - Tušek Bunc, Ksenija (2018)
Instructions for the Subject Family Medicine I. With Family Practice Guidelines I would like to give a comprehensive view of the course of instruction on Family Medicine I in the 4th year, and at the same time, the guidelines should provide effective assistance to both students in teaching and teachers in teaching. At the beginning, we defined goals in Family Medicine I, more specifically, we talked about the implementation of lessons in lectures, seminars in the faculty and in the family medicine clinics. We devoted a special chapter to the obligations of students and teachers. In the end, we have also provided the instructions with an annex, which includes all the more important forms that we need to carry out the lesson.
Keywords: Students; teachers; Family medicine I; study material; study subject